Good practices for 68Ga radiopharmaceutical production - Bryce J. B. Nelson; Jan D. Andersson; Frank Wuest; Sarah Spreckelmeyer (EJNMMI Radiopharmacy and Chemistry, 2022)
Abstract Background The radiometal gallium-68 (68Ga) is increasingly used in diagnostic positron emission tomography (PET), with 68Ga-labeled radiopharmaceuticals developed as potential higher-resolution imaging alternatives to traditional 99mTc agents. In precision medicine, PET applications of 68Ga are widespread, with 68Ga radiolabeled to a variety of radiotracers that evaluate perfusion and organ function, and target specific biomarkers found on tumor lesions such as prostate-specific membrane antigen, somatostatin, fibroblast activation protein, bombesin, and melanocortin. Main body These 68Ga radiopharmaceuticals include agents such as [68Ga]Ga-macroaggregated albumin for myocardial perfusion evaluation, [68Ga]Ga-PLED for assessing renal function, [68Ga]Ga-t-butyl-HBED for assessing liver function, and [68Ga]Ga-PSMA for tumor imaging. The short half-life, favourable nuclear decay properties, ease of radiolabeling, and convenient availability through germanium-68 (68Ge) generators and cyclotron production routes strongly positions 68Ga for continued growth in clinical deployment. This progress motivates the development of a set of common guidelines and standards for the 68Ga radiopharmaceutical community, and recommendations for centers interested in establishing 68Ga radiopharmaceutical production. Conclusion This review outlines important aspects of 68Ga radiopharmacy, including 68Ga production routes using a 68Ge/68Ga generator or medical cyclotron, standardized 68Ga radiolabeling methods, quality control procedures for clinical 68Ga radiopharmaceuticals, and suggested best practices for centers with established or upcoming 68Ga radiopharmaceutical production. Finally, an outlook on 68Ga radiopharmaceuticals is presented to highlight potential challenges and opportunities facing the community.